Role of Honey as Dressing Material in Oral Cavity - IKRAM, R; KHAN, S A; CHEEMA, M S (Annals of King Edward Medical University, 2018)
The treatment of dry socket was evaluated in 62 patients. Honey dressing proved to be analgesic and curative.